El peróxido de hidrógeno y la clorhexidina como enjuagues bucales previos a la atención odontológica para la reducción de la carga viral SARS-CoV- 2 en el aerosol dental. Revisión bibliográfica - Loyola García, Paula Elizabeth (2023)
The COVID-19 disease caused by the SARS-CoV-2 virus, declared a pandemic by the World Health Organization (WHO) on March 11, 2020, is a viral infectious respiratory disease that is transmitted through direct contact and indirect through contaminated fluids such as saliva, secretions and respiratory droplets. Causing dental care to pose a risk for contagion with the SARS-CoV-2 virus for both professionals and patients, due to the generation of aerosols from dental instruments, which, when combined with infected saliva or blood, spread pathogenic microorganisms to the outside of the patient's mouth. Within the biosecurity measures for dental care in times of pandemic, the use of antiseptic mouthwashes prior to care is recommended to favor the reduction of the virus in the oral cavity. That is why the present investigation aimed to compare the virucidal efficacy of hydrogen peroxide and chlorhexidine mouthwashes for the reduction of the SARS-COV-2 viral load, through a bibliographic review. The research was analytical, descriptive and bibliographical, with a quantitative approach, for its structuring a search of 20 scientific articles and theses was carried out in the Medline/PubMed, Google Scholar, Scielo, Elsevier, Scopus and SpringerLink databases and national and international repositories. After performing the analysis, it was concluded that the hydrogen peroxide mouthwash has an efficacy of 59.54% and the chlorhexidine mouthwash has an efficacy of 64.98%, with a difference that is not statistically significant, therefore both mouthwashes are effective for the reduction of SARS- CoV-2 viral load